Mitochondrial Dysfunction in Metabolic Disease - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Mitochondrial function and behavior are central to the physiology of humans and, consequently,